2022
DOI: 10.3390/admsci12030099
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Structural Effect of Achievement Motivation and Achievement on Leadership and Entrepreneurial Spirit of Students in Higher Education

Abstract: Today, it can be seen in the real world that many students are unemployed after graduating from college or university. Two soft skills are taught to determine the success of graduates at work, namely leadership and entrepreneurial spirit. The purpose of this study was to examine the structural effect of achievement motivation and achievement on student leadership and entrepreneurial spirit. This research was conducted in Indonesia, with a total sample of 789 students, through random sampling. Questionnaires an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
1
8
0
1
Order By: Relevance
“…For example, research by Heydari et al (2013) found that achievement motivation positively and significantly influences entrepreneurial intentions in university students. Similar results were also found in research by Wiyono and Wu (2022), which shows that achievement motivation has a positive influence on entrepreneurial intentions among students. In addition to influencing entrepreneurial intentions, achievement motivation can also influence one's career choices.…”
Section: Achievement Motivationsupporting
confidence: 88%
See 2 more Smart Citations
“…For example, research by Heydari et al (2013) found that achievement motivation positively and significantly influences entrepreneurial intentions in university students. Similar results were also found in research by Wiyono and Wu (2022), which shows that achievement motivation has a positive influence on entrepreneurial intentions among students. In addition to influencing entrepreneurial intentions, achievement motivation can also influence one's career choices.…”
Section: Achievement Motivationsupporting
confidence: 88%
“…This exemplifies the impact of community support on students' drive to attain academic success. In addition, scholarly research conducted by Banu and Baral (2022); Wiyono and Wu (2022) suggests that community-based social support plays a significant role in assisting students in surmounting barriers and navigating problems encountered in the pursuit of their objectives. Supportive communities play a crucial role in facilitating the establishment of robust social networks for students, enabling them to readily access assistance and guidance when confronted with challenges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It significantly determines students' educational attainment and functional performance (McClelland, 2000;Steinmayr, Weidinger, Schwinger, & Spinath, 2019). It also affects students' future success or failure since the reason for achieving learning outcomes is often solid motivation (Mahato & Barman, 2019;Sikhwari, 2014;Wiyono & Wu, 2022;Zambuk, 2021).…”
Section: Academic Achievement Motivationmentioning
confidence: 99%
“…Since the emergence of the concept of "knowledge-based economy" and the following concept of the "third academic revolution", universities have been even more expected to contribute to economic and technology growth (Geuna 1999). Concerning academic research on the topic, the endogenous growth theory (Lucas 1988;Romer 1990;Grossman and Helpman 1991), the "National Systems of Innovation" approach (Freeman 1987;Lundvall 1992;Nelson 1993;Wiyono and Wu 2022), or the introduction of the Tripple-Helix model (Etzkowitz and Leydesdorff 1995;Etzkowitz and Leydesdorff 2000) had discussed the university role in supporting the emergence of innovation in the external (non-academic) environment and established a framework for understanding the role of basic research on economic growth and highlighted the human capital dimension of the technological progress. Coming out of the open innovation paradigm, enterprises are pushed to keep their innovation process open to the external environment in order to be more competitive (Mansfield 1995;Vidal et al 2022).…”
Section: Introductionmentioning
confidence: 99%